Maleic anhydride polyethylene octene elastomer toughened polyamide 6/polypropylene nanocomposites : mechanical and morphological properties - Hassan, Azman; Othman, Norhayani; Wahit, Mat Uzir; Lim, Jian Wei; Rahmat, Abdul Razak; Mohd. Ishak, Zainal Ariffin (Wiley-VCH Verlag Berlin, 2006)
A series of polyamide 6/polypropylene (PA6/PP) blends and nanocompo-sites containing 4 wt% of organophilic modified montmorillonite (MMT) were designed and prepared by melt compounding followed by injection molding. Maleicanhydride polyethylene octene elastomer (POEgMAH) was used as impact modifier aswell as compatibilizer in the blend system. Three weight ratios of PA6/PP blends were prepared i.e. 80:20, 70:30, and 60:40. The mechanical properties of PA6/PP blends and nano composite were studied through flexural and impact properties. Scanning electron microscopy (SEM) was used to study the micro structure. The incorporation of 10 wt% POEgMAH into PA6/PP blends significantly increased the toughness with a corresponding reduction in strength and stiffness. However, on further addition of 4wt% organoclay, the strength and modulus increased but with a sacrifice in impact strength. It was also found that the mechanical properties are a function of blend ratio with 70:30 PA6/PP having the highest impact strength, both for blends and nano composites. The morphological study revealed that within the blend ratio studied, the higher the PA6 content, the finer were the POEgMAH particles.